Population Dynamics of Butterflies from Two Selected Areas of South Goa, India - Gadkar, Khushi; Parishwadi, Rifa Irfan; Paul, Sheena; Silveira, Juliana; Kulkarni, Rajender Rao (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Biodiversity issues are very crucial in preventing the permanent extinction of variety of species on the planet earth. Butterflies, moths and skippers are included in the order Lepidoptera. There are about 10% butterfly species of Lepidoptera. Butterflies are well known for their diversity in shape, size and beautiful wing colours, having slender bodies and antennae with club-like tips. In general, in butterflies the wings are held vertically when at rest. They are cosmopolitan in distribution, found everywhere around the world except near the poles. They are diurnals. Our country is gifted with rich butterfly diversity but due to various anthropogenic activities, they are gradually depleting from certain habitats. We have to take appropriate measures to bring them back to optimum level. For this, protection, preservation and propagation are the most sought activities. First and foremost, the important act in this direction is making an inventory of butterfly diversity in the selected and significant habitats. Present investigation is aimed to understand the status of butterfly diversity in the state of Goa, one of the smallest states of the Indian Union and exploring conservation practices. Hence, the present study was undertaken to provide baseline information on the checklist of butterflies and their diversity in Quepem and Sanguem talukas of South Goa. In Quepem, Grey County and Brush-footed Butterfly recorded least relative abundance of 2.991, Grey pansy recorded maximum relative abundance of 6.196. In Sanguem, Nymphalid butterfly, Statira sulphur recorded maximum relative abundance of 3.835 and White peacock recorded least relative abundance of 2.191. Total butterfly abundance at different selected sites of Quepem is Borimal; 31.19, Xeldem; 26.70, Nanda Lake; 20.08, Palacio do deao; 22.00 and Sanguem is Selaulim dam; 25.47, Pattem; 21.09, Kotto ;27.67, Vorcotto; 25.75 during the survey period.